Synthesis and elucidation of local structure in phase-controlled colloidal tin phosphide nanocrystals from aminophosphines. Issue 1 (22nd November 2022) - Paredes, Ingrid J.; Ebrahim, Amani M.; Yanagi, Rito; Plonka, Anna M.; Chen, Shuzhen; Xia, Hanlu; Lee, Scott; Khwaja, Mersal; Kannan, Haripriya; Singh, Ajay; Hwang, Sooyeon; Frenkel, Anatoly I.; et al.
Abstract : Aminophosphines are a class of inexpensive, environmentally benign phosphorus precursors that have provided routes to various metal phosphides. In this work, we use the aminophosphine tris(diethyl)aminophosphine to synthesize tin phosphide nanocrystals. Abstract : The chemical versatility and rich phase behavior of tin phosphides has led to interest in their use for a wide range of applications including optoelectronics, thermoelectrics, and electrocatalysis. However, researchers have identified few viable routes to high-quality, phase-pure, and phase-controlled tin phosphides. An outstanding issue is the small library of phosphorus precursors available for synthesis of metal phosphides. We demonstrated that inexpensive, commercially available, and environmentally benign aminophosphines can generate various phases of colloidal tin phosphides. We manipulated solvent concentrations, precursor identities, and growth conditions to obtain Sn3 P4, SnP, and Sn4 P3 nanocrystals. We performed a combination of X-ray diffraction and transmission electron microscopy to determine the phase purity of our samples. X-ray absorption spectroscopy provided detailed analyses of the local structures of the tin phosphides.